2023
DOI: 10.1111/jebm.12549
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancement in integrating artificial intelligence and information technology with real‐world data for clinical decision‐making in China: A scoping review

Xiwen Liao,
Chen Yao,
Jun Zhang
et al.

Abstract: ObjectiveStriking innovations and advancements have been achieved with the use of artificial intelligence and healthcare information technology being integrated into clinical real‐world data. The current scoping review aimed to provide an overview of the current status of artificial intelligence‐/information technology‐based clinical decision support tools in China.MethodsPubMed/MEDLINE, Embase, China National Knowledge Internet, and Wanfang data were searched for both English and Chinese literature. The gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…This can help provide faster and more reliable diagnosis and reduce human errors. 28 , 29 , 34 , 36 - 38 , 43 , 45 , 52 Besides that, AI has shown the capability to streamline the drug prescription process. 31 Moreover, one paper reported that AI can aid in patient triage by offering guidance and evaluating the severity and priority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This can help provide faster and more reliable diagnosis and reduce human errors. 28 , 29 , 34 , 36 - 38 , 43 , 45 , 52 Besides that, AI has shown the capability to streamline the drug prescription process. 31 Moreover, one paper reported that AI can aid in patient triage by offering guidance and evaluating the severity and priority of cases.…”
Section: Discussionmentioning
confidence: 99%